Flavonoids from the genus Polygonatum: biological activities and biosynthesis mechanism - Ye, Xin-Pei; Hu, Yan-Yu; Chen, Yan-Xi; Tang, Zhen-Xing; Jiang, Zhong-Bao; Fu, Yue; Wang, Zi-Xin; Pi, Er-Xu; Bian, Gao-Feng; Shi, Lu-E (Frontiers in Nutrition, 2025)
The genus Polygonatum is a medicinal plant that has been used as food for a long time, containing various biologically active compounds, including polysaccharides, saponins, flavonoids, alkaloids, and many others. Polygonatum, like other Chinese herbal plants, can be employed as natural medicines, exhibiting a reduced incidence of adverse effects compared to synthetic pharmaceuticals. Flavonoids are key biomarkers that indicate the quality of the genus Polygonatum, and constitute one of the primary active ingredients. Additionally, flavonoids exhibit a range of nutritional, biological and health-promoting characteristics, including antibacterial, antioxidant, anti-inflammatory, antitumor, and hypoglycemic properties. This paper reviewed biosynthesis and bioactivities of flavonoids from the genus Polygonatum. We hope that this paper would ultimately serve as a valuable reference for the development of flavonoid-related functional foods from the genus Polygonatum.